Molecular phylogeny of two Rhinoxenus species (Monogenea: Dactylogyridae) from the nasal cavities of serrasalmids (Characiformes: Serrasalmidae) from Brazil - Osaki-Pereira, Melissa Miyuki [UNESP]; Narciso, Rodrigo Bravin [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Müller, Maria Isabel; Ebert, Mariana Bertholdi [UNESP]; da Silva, Reinaldo José [UNESP] (Springer Nature, 2023)
The dactylogyrid genus Rhinoxenus (Monogenea: Dactylogyridae) is composed of specialized monogeneans infecting the nasal cavities of freshwater fishes from the Neotropical region. This taxon currently comprises 11 species and is easily distinguished from other monogeneans by the absence of the dorsal bar, ventral anchor with inconspicuous roots covered by a sclerotized cap, dorsal anchor greatly modified into a needle-like shape, and hook pair 2 located into bilateral lobes of the trunk. Specimens of Rhinoxenus euryxenus and Rhinoxenus paranaensis were found infecting the nasal cavities of Serrasalmus marginatus and Serrasalmus maculatus, respectively, from the Paraná River basin in Brazil. For the first time, molecular data of Rhinoxenus spp. were obtained and used as a basis for phylogenetic analyses of the genus. Furthermore, our findings represent the first record of R. paranaensis in Brazil.